A study of dentists’ preferences for the restoration of shortened dental arches with partial dentures - Nassani, Mohammad Zakaria; Ibraheem, Shukran; Al-Hallak, Khaled Rateb; El Khalifa, Mohammed Othman Ali; Baroudi, Kusai (European Journal of Dentistry, 2015)
Objective: This study aimed to use a utility method in order to assess dentists’ preferences for the restoration of shortened dental arches (SDAs) with partial dentures. Also, the impact of patient age and length of the SDA on dentists’ preferences for the partial dentures was investigated. Materials and Methods: Totally, 104 subjects holding a basic degree in dentistry and working as staff members in a private dental college in Saudi Arabia were interviewed and presented with 12 scenarios for patients of different ages and mandibular SDAs of varying length. Participants were asked to indicate on a standardized visual analog scale how they would value the health of the patient's mouth if the mandibular SDAs were restored with cobalt-chromium removable partial dentures (RPDs). Results: With a utility value of 0.0 representing the worst possible health state for a mouth and 1.0 representing the best, dentists’ average utility value of the RPD for the SDAs was 0.49 (sd= 0.15). Mean utility scores of the RPDs across the 12 SDA scenarios ranged between 0.35 and 0.61. RPDs that restored the extremely SDAs attracted the highest utility values and dentists’ utility of the RPD significantly increased with the increase in the number of missing posterior teeth. No significant differences in dentists’ mean utility values for the RPD were identified among SDA scenarios for patients of different ages. Conclusion: Restoration of the mandibular SDAs by RPDs is not a highly preferred treatment option among the surveyed group of dentists. Length of the SDA affects dentists’ preferences for the RPD, but patient age does not.
Keywords: Dentists; partial denture; preferences; shortened dental arch; utility